A novel architecture for cooperative remote rehabilitation system. (November 2016) - Koochaki, Fateme; Sharifi, Iman; Talebi, Heidar A.
Abstract: In this paper, the problem of trilateral interaction between therapist, patient, and virtual environment is considered. Herein, a new architecture for robotic rehabilitation is investigated based on the robots together with patient and therapist, cooperating with each other to accomplish the therapy in the virtual reality, in which the rehabilitation system is divided into three subsystems: patient, therapist, and virtual environment. Each subsystem is controlled locally, ensuring that it is input-to-state stable (ISS). Besides, the associated interconnections are shown to be stable in the presence of communication time delays. First, the patient is capable of generating movements until losing his strength, i.e. interacting with the robot without help of the therapist. Afterwards, the therapist assists the patient to follow up the process, i.e. the patient is active in the former condition while becomes passive in the latter. Therefore, the controllers should be able to deal with not only active but also passive robots. Also, impedance reflection, adaptive projection method, and impedance control are utilized. Finally, simulation and experimental results are extracted in evaluation.